I’ll tell you a secret: socialization into oral social practices in elementary school whole group interaction - Malabarba, Taiane; de Souza, Joseane (Revista da ABRALIN, 2022)
This paper investigates socialization into classroom whole-group participation from an interactional and micro-analytic perspective. Drawing on the single case of a moment of explicit socialization into the participation norms of elementary-school classroom interaction, it shows how such norms become a ‘learnable’, i.e., the object of teaching/learning. Specifically, it demonstrates in detail how a teacher turns a single student’s complaint related to the student’s trouble accessing the floor into an opportunity to socialize the group of students into the practice of raising hands to bid for the floor and waiting until being selected to deliver a turn-at-talk. This includes avoiding treating the complaint as a matter for reproaching the students who are not following the norms, and instead, explicitly stating the interactional trajectory of what constitutes - from the teacher perspective - a successful manner to get access to the floor and contributing to the whole-group discussion. The analysis of the sequence organization of talk during this moment unpacks the multifaceted and contingent nature of the teaching and learning of oral social practices and unveils 1) divergent orientations and methods for managing and contributing to the classroom talk; and 2) underlying moral issues connected both with the student’s complaint and with how it is treated by the teacher. The findings resulting from the fine-grained analysis of a unique episode allow for discussion on broader social issues, such as asymmetry and morality. They constitute a potentially relevant resource for further research on other cases and contexts, and for professional reflection as well.